2013
DOI: 10.1016/j.seizure.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics and seizures: Higher risk with atypicals?

Abstract: Our results show that SGA may pose a higher risk of seizures than FGA, mainly, but not only due to clozapine. This is line with recent studies suggesting that some SGA carried a higher average risk of electroencephalographic abnormalities than many FGA. Nonetheless, It is well known that spontaneous reports do not allow strong inferences about adverse drug effects, because differences in reporting fractions by time, drug or type of event are difficult or even impossible to distinguish from differences in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 10 publications
(11 reference statements)
1
49
2
3
Order By: Relevance
“…1b, 2, 3a). Our data are in agreement with that observed in human therapy where haloperidol is one of the agents with the least seizure-induction activity among antipsychotics [8].…”
Section: Haloperidolsupporting
confidence: 92%
See 4 more Smart Citations
“…1b, 2, 3a). Our data are in agreement with that observed in human therapy where haloperidol is one of the agents with the least seizure-induction activity among antipsychotics [8].…”
Section: Haloperidolsupporting
confidence: 92%
“…1a, b; 2; 3a, c). The latter data are partially in contrast with that observed in human therapy where risperidone is an agent with the lowest seizure induction activity among APs [8]. However, a previous clinical study indicated that risperidone overdose is able to induce seizures [87].…”
Section: Risperidonementioning
confidence: 68%
See 3 more Smart Citations